ANALYZE AND IMPROVE PROCESS CAPABILITY USING CONTROL CHART AND FISH BONE DIAGRAM - Zainab Mohammed Abd (Scholars Digest Publishing, 2025)
The research aims to To improve the process's ability to achieve the required design specifications and meet customer requirements in a company of the Iraqi Ministry of Industry and Minerals, the research is based on the research problem of the existence of deviations in the air filter manufacturing process and the exit of some operations from statistical control , as the research method was based on the case study ( Case Study ) and is represented in observation, personal interviews, field experience and the use of the inspection list with the intention of Access to scientific facts that help in comprehensive and realistic analysis to reach scientific facts The research results showed that the company's quality control department lacks qualified personnel to use quality management tools, including the fishbone test, which helps in identifying the roots of problems, defects, and failures in production lines.
Keywords: Process capability, fishbone, control panels.